A suggested curriculum for musical appreciation in Art Education Departments - Faculties of Fine Arts: فاضل عرام لازم (Al-Academy, 2021)
The Department of Art Education in the College of Fine Arts is one of the educational institutions that aims to prepare teachers specialized in teaching art education in secondary schools and other educational institutions, which forces those in charge of preparing the curricula for this section and developing it, taking into account the rapid scientific and technological development. And the subject (Music Appreciation) is one of the subjects taught for the third grades in Art Education departments, and through the exploratory study carried out by the researcher it became clear to him that the Faculties of Fine Arts agreed to define their educational objectives and outputs in the subject (Music Appreciation) in Art Education departments, but they did not agree In preparing a unified curriculum vocabulary for this subject, which prompted the researcher to prepare a proposed curriculum for the subject of musical appreciation for the departments of art education in the Faculties of Fine Arts, using the curriculum vocabulary taught in these departments. The first chapter included the objective of the research: Preparing a proposed curriculum for the subject of musical appreciation in the departments of art education in the Faculties of Fine Arts in Iraqi universities, in light of the objectives set for each department and the vocabulary taught in it. The second chapter included the themes: curriculum, objectives, and musical appreciation. The fourth chapter included: the procedures followed by the researcher in preparing the proposed curriculum and building the research tool. As for the fourth chapter, it includes the results of the research that have been achieved by preparing the proposed curriculum for the subject (musical appreciation) in the departments of art education - Faculties of Fine Arts in Iraq, through the procedures carried out by the researcher in the third semester, and in light of the results the researcher concluded the following:1. The curriculum for the subject (Musical Appreciation), which is taught in Art Education departments, was prepared without reference to experts who are specialized in the educational, artistic, and applied fields in the field of musical arts.2. The need to improve the curriculum of the subject (musical appreciation) in order to raise the level of its objectives and vocabulary to the level at which it meets the valid standards of the applied curricula, and thus conforms to the developments in this field.As for the recommendations, they were: The necessity of reviewing well-known world classifications, in the cognitive, emotional and skillful aspects, in order to build an integrated approach to the subject of musical appreciation. Then the proposals